2019
DOI: 10.1021/acs.langmuir.9b01979
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Mapping of the Physical Surface Properties of Human Buccal Cells and Changes Induced by Saliva

Abstract: The mucosal pellicle, also called salivary pellicle, is a thin biological layer made of salivary and epithelial constituents, lining oral mucosae. It contributes to their protection against microbiological, chemical or mechanical insults. Pellicle formation depends on the cells' surface properties, and in turn the pellicle deeply modifies such properties. It has been reported that the expression of the transmembrane mucin MUC1 in oral epithelial cells improves the formation of the mucosal pellicle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 31 publications
0
25
0
3
Order By: Relevance
“…The different effect of polyphenols on guaiacol volatility in wines spiked with BC compared to wines with AS could be due to the different hydrophobic properties of BC. As said before, the presence at the surface of the oral cells of highly hydrophobic and hydrophilic domains due to the expression of different types of mucin [33] might differently affect the binding of different types of phenolic compounds to BC, which in turn might also affect the interaction with guaiacol.…”
Section: Effect Of Phenolic Compounds On Aroma Volatility In Wines Wimentioning
confidence: 89%
See 2 more Smart Citations
“…The different effect of polyphenols on guaiacol volatility in wines spiked with BC compared to wines with AS could be due to the different hydrophobic properties of BC. As said before, the presence at the surface of the oral cells of highly hydrophobic and hydrophilic domains due to the expression of different types of mucin [33] might differently affect the binding of different types of phenolic compounds to BC, which in turn might also affect the interaction with guaiacol.…”
Section: Effect Of Phenolic Compounds On Aroma Volatility In Wines Wimentioning
confidence: 89%
“…This polar compound could be salted out by the addition of BC, which could modify its solubility in the wine. Actually, using a model of oral epithelial cells, it has been shown that the surface of the oral cells present both highly hydrophobic and hydrophilic domains due to the different expression of MUC1/Y-LSO mucin [33]. The expression of MUC1 results in the presence of more hydrophobic and more charged areas at the cell surface [33].…”
Section: Effect Of Oral Components On Wine Aroma Volatilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the objective of this work is to combine new investigation methods for local determination of the RS field, targeting the two kinds of stress mentioned above. The first method is the Raman micro-spectroscopy, which is increasingly used in this field [9][10][11][12][13][14]. This technology enables fast micro-scale measurements on Raman-active materials such as oxides [9,10].Here, lattice bondings will be submitted to vibration through the inelastic photon scattering phenomenon using a low power laser emission.…”
Section: Purpose Of the Workmentioning
confidence: 99%
“…A more complete theory is available in "Experimental Section" of Aybeke, EN and al. paper [14]. This in-depth technique represents a significant change in stress investigation, especially when dealing with ceramic coatings.…”
Section: Purpose Of the Workmentioning
confidence: 99%